2021
DOI: 10.3390/medicina57090941
|View full text |Cite
|
Sign up to set email alerts
|

Knee-High Devices Are Gold in Closing the Foot Ulcer Gap: A Review of Offloading Treatments to Heal Diabetic Foot Ulcers

Abstract: Diabetic foot ulcers (DFU) are a leading cause of the global disease burden. Most DFUs are caused, and prolonged, by high plantar tissue stress under the insensate foot of a person with peripheral neuropathy. Multiple different offloading treatments have been used to try to reduce high plantar tissue stress and heal DFUs, including bedrest, casting, offloading devices, footwear, and surgical procedures. The best offloading treatments are those that balance the benefits of maximizing reductions in high plantar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 117 publications
(428 reference statements)
0
29
0
Order By: Relevance
“…Pressure offloading aims to reduce high plantar tissue stress and has been found to be critical to achieve timely and complete DFU healing [ 1 , 9 , 11 ]. To do this effectively, offloading should maximise the desirable effects (benefits) of reducing high plantar tissue stress; whilst also minimising any undesirable effects (risks), such as adverse events and high costs [ 10 , 12 , 13 ]. Various offloading treatments have been used clinically, including offloading devices, footwear and corrective surgery [ 12 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pressure offloading aims to reduce high plantar tissue stress and has been found to be critical to achieve timely and complete DFU healing [ 1 , 9 , 11 ]. To do this effectively, offloading should maximise the desirable effects (benefits) of reducing high plantar tissue stress; whilst also minimising any undesirable effects (risks), such as adverse events and high costs [ 10 , 12 , 13 ]. Various offloading treatments have been used clinically, including offloading devices, footwear and corrective surgery [ 12 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous reviews in the area have found that NRKHDs reduce more PP than other offloading treatments by incorporating more key mechanical features, such as customized insoles/foot-device interfaces, rocker-bottom soles, controlled ankle motion, and higher cast walls/struts preferably extending up to the knee. 20 These features typically also reduce foot and ankle joint movements [21][22][23] and subsequent horizontal shear forces by using the contact surfaces as loadbearing surfaces. 24 In addition, restricted ankle movement will necessitate strategies of reducing mobility and/or increasing requirements on the contralateral limb.…”
Section: Reduction Of Pp and Shear Stress At The Dfumentioning
confidence: 99%
“…51,55 Existing knee-high offloading devices can be hot to wear. 20 Already, 3D-printed ankle fracture casts and cervical orthoses with improved ventilation have been designed to improve patient comfort 56,57 which could easily be translated to offloading device design. Hence, it may be possible to create a personalized device from a 3D scan that is lighter, has improved ventilation, and effectively reduces plantar tissue stresses.…”
Section: Advanced Manufacturing Enables Personalized Device Designsmentioning
confidence: 99%
“…In addition, recommended exercises are those that help develop joint mobility and reduce plantar pressure. Another important measure is custom footwear, used for pressure relief and adapted to the patient’s lesion [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%